Aldose reductase inhibitors: 2013-present. (4th March 2019) - Quattrini, Luca; La Motta, Concettina
ABSTRACT: Introduction : Aldose reductase (ALR2) is both the key enzyme of the polyol pathway, whose activation under hyperglycemic conditions leads to the development of chronic diabetic complications, and the crucial promoter of inflammatory and cytotoxic conditions, even under a normoglycemic status. Accordingly, it represents an excellent drug target and a huge effort is being done to disclose novel compounds able to inhibit it. Areas covered : This literature survey summarizes patents and patent applications published over the last 5 years and filed for natural, semi-synthetic and synthetic ALR2 inhibitors. Compounds described have been discussed and analyzed from both chemical and functional angles. Expert opinion : Several ALR2 inhibitors with a promising pre-clinical ability to address diabetic complications and inflammatory diseases are being developed during the observed timeframe. Natural compounds and plant extracts are the prevalent ones, thus confirming the use of phytopharmaceuticals as an increasingly pursued therapeutic trend also in the ALR2 inhibitors field. Intriguing hints may be taken from synthetic derivatives, the most significant ones being represented by the differential inhibitors ARDIs. Differently from classical ARIs, these compounds should fire up the therapeutic efficacy of the class while minimizing its side effects, thus overcoming the existing limits of this kind of inhibitors.